KAJIAN SUFISTIK DALAM NOVEL MERINDU BAGINDA NABI KARYA HABIBURRAHMAN EL SHIRAZY PERSPEKTIF TASAWUF IMAM AL-GHAZALI - Bahri, Shahibul; Moh Juhdi; Salamet (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the Sufistic values contained in Habiburrahman El Shirazy's novel Merindu Baginda Nabi through the perspective of Imam AlGhazali's Sufistic theory. The research is qualitative descriptive employing a literary analysis approach. The primary data source is the novel Merindu Baginda Nabi, while secondary sources include Al-Ghazali's classical works and contemporary scientific articles discussing Islamic mysticism. Data were collected through intensive reading, note-taking, classification, and interpretation based on Al-Ghazali's concepts of taubah (repentance), sabr (patience), syukur (gratitude), tawakal (trust in God), mahabbah (love), ma'rifah (gnosis), and tazkiyatun nafs (purification of the soul). The findings indicate that the novel presents Sufistic values not merely as religious discourse but as a practical way of life embodied by the characters. The spiritual journey portrayed in the novel reflects a gradual process of self-purification leading to spiritual maturity. The longing for the Prophet Muhammad is represented not only as emotional affection but also as ethical imitation through sincere worship, compassion, humility, and social responsibility. Consequently, the novel contributes significantly to contemporary Islamic literature by integrating narrative aesthetics with Sufistic teachings, making spiritual values accessible to modern readers.